Analgesic, neuropharmacological, anti-diarrheal, and cytotoxic activities of the extract of Solanum sisymbriifolium (Lam.) leaves - Apurba Sarker Apu; Shakhawat Hossan Bhuyan; Maima Matin; Md. Faruq Hossain; Farjana Khatun; Abu Taiab Md. Jamaluddin (Mashhad University of Medical Sciences, 2013)
Objective: The present study was undertaken to evaluate the possible analgesic, neuropharmacological, anti-diarrheal, and cytotoxic activities of the ethanol extract of leaves of Solanum sisymbriifolium Lam. (Family: Solanaceae). Materials and Methods: The analgesic activity was measured by acetic acid-induced writhing inhibition test. The neuropharmacological activities were evaluated using hole cross, hole board, and elevated plus-maze test and the anti-diarrheal activity was assessed using castor oil-induced diarrhea inhibition method. Brine shrimp lethality bioassay was carried out for assessing the cytotoxicity of the ethanol extract of the leaves. Except cytotoxic activity, all the tests were conducted on mice. Results: The extract at oral doses of 200 and 400 mg/kg body weight showed highly significant (p